Patenting of pharmaceutical drugs: Does it guarantee access to medicine? - DR.P.R.L.RAJAVENKATESAN; DR.E.PREMA (International Journal of Pharma and Bio Sciences, 2017)
Intellectual property rights have been considered as most valuable assets in the technological driven era. The rights of the creators, authors and inventors etc., are being streamlined in such a way to reap the benefits of the same. Among various kinds of intellectual property rights existing in the digitalized era, pharmaceutical invention is one kind of it. The term patent itself is buzz word and getting the drugs to be patented is a subject of controversies because of ever greening methodology adopted by the pharmaceutical giant in worldwide. The present research paper is intended to focuses on patentable subject matter in general and pharmaceutical drugs in particular.